Just Grace walks the dog - Harper, Charise Mericle (Boston : Houghton Mifflin Harcourt, 2008)
Eight-year-old Just Grace and her best friend Mimi embark on a campaign to convince Grace's parents that they are responsible and dependable enough to get a dog.
"Sandpiper."
Horn Book
Kirkus Review
School Library Journal
Horn Book, October 2008
Kirkus Review, March 2008
Keywords: Diaries -- Juvenile fiction; Dogs -- Juvenile fiction; Responsibility -- Juvenile fiction; Schools -- Juvenile fiction; Diaries -- Fiction; Dogs -- Fiction; Responsibility -- Fiction; Schools -- Fiction; Diaries -- Fiction; Dogs -- Fiction; Responsibility -- Fiction; School stories